A Validation Argument for a Simulation-Based Training Course Centered on Assessment, Recognition, and Early Management of Pediatric Sepsis. Issue 1 (February 2018) - Geis, Gary L.; Wheeler, Derek S.; Bunger, Amy; Militello, Laura G.; Taylor, Regina G.; Bauer, Jerome P.; Byczkowski, Terri L.; Kerrey, Benjamin T.; Patterson, Mary D.
Abstract : Introduction: Early recognition of sepsis remains one of the greatest challenges in medicine. Novice clinicians are often responsible for the recognition of sepsis and the initiation of urgent management. The aim of this study was to create a validity argument for the use of a simulation-based training course centered on assessment, recognition, and early management of sepsis in a laboratory-based setting. Methods: Five unique simulation scenarios were developed integrating critical sepsis cues identified through qualitative interviewing. Scenarios were piloted with groups of novice, intermediate, and expert pediatric physicians. The primary outcome was physician recognition of sepsis, measured with an adapted situation awareness global assessment tool. Secondary outcomes were physician compliance with pediatric advanced life support (PALS) guidelines and early sepsis management (ESM) recommendations, measured by two internally derived tools. Analysis compared recognition of sepsis by levels of expertise and measured association of sepsis recognition with the secondary outcomes. Results: Eighteen physicians were recruited, six per study group. Each physician completed three sepsis simulations. Sepsis was recognized in 19 (35%) of 54 simulations. The odds that experts recognized sepsis was 2.6 [95% confidence interval (CI) = 0.5–13.8] times greater than novices. Adjusted for severity, for every point increase in the PALS global performance score, the odds that sepsis was recognized increased by 11.3 (95% CI = 3.1–41.4). Similarly, the odds ratio for the PALS checklist score was 1.5 (95% CI = 0.8–2.6). Adjusted for severity and level of expertise, the odds of recognizing sepsis was associated with an increase in the ESM checklist score of 1.8 (95% CI = 0.9–3.6) and an increase in ESM global performance score of 4.1 (95% CI = 1.7–10.0). Conclusions: Although incomplete, evidence from initial testing suggests that the simulations of pediatric sepsis were sufficiently valid to justify their use in training novice pediatric physicians in the assessment, recognition, and management of pediatric sepsis. Abstract : Supplemental digital content is available in the text.